Implementierung der Hybrid-NOTES-Sigmoidektomie bei Divertikelkrankheit: in einem Zentrum für minimalinvasive Chirurgie - Steinemann, Daniel; Zerz, Andreas; Lamm, Sebastian (Der Chirurg, 2017)
Background: Natural orifice transluminal endoscopic surgery (NOTES) describes surgical procedures through a natural orifice. In hybrid-NOTES small transabdominal trocars are combined with a NOTES access.ObjectiveTo evaluate hybrid-NOTES sigmoidectomy as a standard procedure for diverticulitis.Material and methods: Elective laparoscopic sigmoidectomies performed between May 2011 and January 2016 were prospectively collated. Primary endpoint was the feasibility of hybrid-NOTES sigmoidectomy. The reasons for planning a laparoscopically-assisted sigmoidectomy (LAS), intraoperative change of treatment and reactive conversion were evaluated. Secondary endpoints were complications and operative time. Results: Out of 130 laparoscopic sigmoidectomies 83% were planned for hybrid-NOTES and 8 out of 52 (15%) transvaginal (TVS) and 14 out of 56 (25%) transrectal (TRS) sigmoidectomies were intraoperatively changed to LAS. The reason for the change in 64% was that the specimen was too bulky and 80% of scheduled hybrid-NOTES procedures were carried out as planned. The operative time for TVS (146.8 ± 44.5 min) was shorter compared to LAS (173.2 ± 58.8 min, P = 0.016). The morbidities of TVS (15.3%) and TRS (14.9%) were not significantly different from LAS (23.9%, P = 0.501 and P = 0.537, respectively). Conclusion: Hybrid-NOTES for diverticular disease may be indicated in more than 80% of cases. In respect of intraoperative change of treatment, hybrid-NOTES is feasible in two thirds of patients. Given a high level of expertise, hybrid-NOTES can be provided as a standard procedure in sigmoidectomy for diverticular disease.
First online: 07 December 2016
Gesehen am 18.09.2018